Trevor rides Jake piggyback II

Calculus Level 4

It's a beautiful Sunday morning. The wind is calm but fills one with energy, the sun warm and yellow, and the Trevor is riding Jake piggyback upon the lush green turf of the golf course.

Starting at ( 0 , 0 ) (0,0) , Trevor tells his serf to advance by n 2 n \dfrac{n}{2^{n}} meters and turn 9 0 90^{\circ} clockwise at the nth step.

What is the distance Trevor and Jake have travelled from the origin? If your answer is of the form a b \frac{a}{b} where a a and b b are positive coprime integers, find a + b a+b .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Utsav Banerjee
May 18, 2015

Since we require the distance of the final position from the origin ( 0 , 0 ) (0,0) , we can assume without loss of generality that the first step is upwards, that is, in the positive y-direction. Therefore, the x & y coordinates of the final position ( X f , Y f ) (X_{f}, Y_{f}) are given by the following expressions:

X f = 2 2 2 4 2 4 + 6 2 6 8 2 8 + X_{f}=\frac{2}{2^2}-\frac{4}{2^4}+\frac{6}{2^6}-\frac{8}{2^8}+\cdots

Y f = 1 2 3 2 3 + 5 2 5 7 2 7 + Y_{f}=\frac{1}{2}-\frac{3}{2^3}+\frac{5}{2^5}-\frac{7}{2^7}+\cdots

The following figure shows how the expressions for X f X_{f} and Y f Y_{f} are derived:

Now, X f = 1 2 n = 1 n ( 1 ) ( n 1 ) 2 2 ( n 1 ) = 1 2 n = 1 k = n ( 1 ) ( k 1 ) 2 2 ( k 1 ) X_{f}=\frac{1}{2} \displaystyle \sum_{n=1}^{\infty} \frac{n(-1)^{(n-1)}}{2^{2(n-1)}}=\frac{1}{2} \displaystyle \sum_{n=1}^{\infty} \displaystyle \sum_{k=n}^{\infty} \frac{(-1)^{(k-1)}}{2^{2(k-1)}}

X f = 1 2 n = 1 [ ( 1 ) ( n 1 ) 2 2 ( n 1 ) × 1 1 ( 1 4 ) ] = 2 5 n = 1 ( 1 ) ( n 1 ) 2 2 ( n 1 ) \Rightarrow X_{f}=\frac{1}{2} \displaystyle \sum_{n=1}^{\infty} [\frac{(-1)^{(n-1)}}{2^{2(n-1)}} \times \frac{1}{1-(-\frac{1}{4})}]=\frac{2}{5} \displaystyle \sum_{n=1}^{\infty} \frac{(-1)^{(n-1)}}{2^{2(n-1)}}

X f = 2 5 × 1 1 ( 1 4 ) = 8 25 \Rightarrow X_{f}=\frac{2}{5} \times \frac{1}{1-(-\frac{1}{4})}=\frac{8}{25}

Next, Y f = 1 2 n = 1 ( 2 n 1 ) ( 1 ) ( n 1 ) 2 2 ( n 1 ) = n = 1 n ( 1 ) ( n 1 ) 2 2 ( n 1 ) 1 2 n = 1 ( 1 ) ( n 1 ) 2 2 ( n 1 ) Y_{f}=\frac{1}{2} \displaystyle \sum_{n=1}^{\infty} \frac{(2n-1)(-1)^{(n-1)}}{2^{2(n-1)}}=\displaystyle \sum_{n=1}^{\infty} \frac{n(-1)^{(n-1)}}{2^{2(n-1)}}-\frac{1}{2} \displaystyle \sum_{n=1}^{\infty} \frac{(-1)^{(n-1)}}{2^{2(n-1)}}

Note that we have already computed both the sums while calculating X f X_{f} . The first sum is equal to 16 25 \frac{16}{25} , and the second sum is equal to 4 5 \frac{4}{5} . Therefore,

Y f = 16 25 ( 1 2 × 4 5 ) = 6 25 Y_{f}=\frac{16}{25}-(\frac{1}{2} \times \frac{4}{5})=\frac{6}{25} .

Therefore, the net displacement from origin is:

S f = X f 2 + Y f 2 = 10 25 = 2 5 S_{f}=\sqrt{X_{f}^{2}+Y_{f}^{2}}=\frac{10}{25}=\frac{2}{5}

Hence, the required answer is 2 + 5 = 7 2+5=\boxed{7}

How did u assume the expression for Xf and Yf ?

batna srikavya - 6 years ago

Log in to reply

I have not assumed it! I have added a figure to the solution to explain how the expressions are derived. Basically, turning 90 degrees clockwise at each step means that you are traveling in a spiral fashion, as shown in the figure. For finding X f X_{f} , we add the lengths of the blue arrows pointing right, and subtract the lengths of the blue arrows pointing left. For finding Y f Y_{f} , we add the lengths of the green arrows pointing up, and subtract the lengths of the green arrows pointing down. The length of each arrow is known from the fact that the distance covered in the n t h n^{th} step is n 2 n \frac{n}{2^{n}} . Hope this clears everything!

Utsav Banerjee - 6 years ago

Log in to reply

Yeah....it's crystal clear now !!! Thank u....

batna srikavya - 6 years ago
Aditya Dhawan
Oct 31, 2016

We see coordinates of the final point are:

( n = 1 ( 1 ) n + 1 2 n x 2 n , n = 1 ( 1 ) n + 1 2 n 1 x 2 n 1 ) D i s p l a c e m e n t = ζ = ( { ( 1 ) n + 1 2 n x 2 n } 2 + { ( 1 ) n + 1 2 n 1 x 2 n 1 } 2 ) L e t f ( x ) = n = 1 n x n f ( x ) f ( x ) x = n = 1 1 x n = 1 x 1 f ( x ) = x ( x 1 ) 2 N o w , f ( i x ) = ( 1 ) n + 1 2 n x 2 n + i n = 1 ( 1 ) n + 1 2 n 1 x 2 n 1 = i x ( i x 1 ) 2 f ( i x ) = ζ = i x ( i x 1 ) 2 = x x 2 + 1 x = 2 = 2 5 \\ \\ \left( \sum _{ n=1 }^{ \infty }{ { (-1) }^{ n+1 }\frac { 2n }{ { x }^{ 2n } } ,\quad \quad \quad \quad \sum _{ n=1 }^{ \infty }{ { (-1) }^{ n+1 } } \frac { 2n-1 }{ { x }^{ 2n-1 } } } \right) \\ \therefore \quad Displacement=\quad \zeta \quad =\quad \sqrt { \left( { \left\{ \sum { { (-1) }^{ n+1 }\frac { 2n }{ { x }^{ 2n } } } \right\} }^{ 2 }+{ \left\{ \sum { { (-1) }^{ n+1 }\frac { 2n-1 }{ { x }^{ 2n-1 } } } \right\} }^{ 2 } \right) \\ } \\ Let\quad f\left( x \right) =\quad \sum _{ n=1 }^{ \infty }{ \frac { n }{ { x }^{ n } } } \\ f\left( x \right) -\frac { f\left( x \right) }{ x } =\quad \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { x }^{ n } } } =\quad \frac { 1 }{ x-1 } \Longrightarrow f\left( x \right) =\frac { x }{ { (x-1) }^{ 2 } } \\ Now,\quad -f(ix)=\quad \sum { { (-1) }^{ n+1 }\frac { 2n }{ { x }^{ 2n } } } +\quad i\sum _{ n=1 }^{ \infty }{ { (-1) }^{ n+1 } } \frac { 2n-1 }{ { x }^{ 2n-1 } } =\quad \frac { ix }{ { (ix-1) }^{ 2 } } \\ \therefore \quad \left| f\left( ix \right) \right| =\quad \zeta \quad =\quad \left| \frac { { ix } }{ { (ix-1) }^{ 2 } } \right| =\quad \underset { x=2 }{ \frac { x }{ { x }^{ 2 }+1 } } =\quad \boxed { \frac { 2 }{ 5 } } \\

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...